Contemporary Britain a survey with texts - Oakland, John
This work is a wide-ranging collection of sources concerning every important aspect of life in Britain today, from national identity to moral panics and offers a snapshot of life in Britain at the beginning of the 21st century. Topics covered include: Britain's role in world affairs; British national identity; constitutional reform within Britain; social institutions including the NHS; political parties; and morality and religion.